PEMBUKTIAN DALAM PERSIDANGAN PERKARA TINDAK PIDANA KORUPSI SECARA TELECONFERENCE DI MASA PANDEMI COVID-19 - Aryaguna (2021)
The trial of corruption cases by teleconference is very vulnerable to manipulation of the trial or game cases that can obscure or change the actual facts, internet network connections. In addition, with atrial teleconference for judges, public prosecutors and legal advisors cannot see the direct response of the examined parties to determine the gesture in answering and giving reasons in answering questions, making it difficult to catch whether there has been a blurring of facts or not. The problems of this research are 1) How is the evidence in the trial of corruption cases by teleconference during the Covid-19 pandemic? 2) How should a case prove a corruption case teleconference during the Covid-19 pandemic? By using normative juridical research methods, it is known that 1) Perma No. 4 of 2020 in principle has accommodated the process of proving the trial of corruption cases and is legal according to law, but in practice not all cases of corruption can be proven by teleconference. 2) The process of proving the trial of corruption cases by teleconference in the Covid-19 pandemic situation that should be carried out is optional so that in practice it does not need to be carried out by teleconference, this returns to the weight of the case being handled.